An observational case series measuring the energy expenditure of elite tennis players during competition and training by using doubly labeled water - Ellis, D. G.; Speakman, J.; Hambly, C.; Morton, J. P.; Close, G. L.; Donovan, T. F. (International Journal of Sports Physiology and Performance, 2023)
Tennis is a sport played across a variety of environmental conditions (temperature, humidity, and altitude), surfaces (hard, grass, and clay courts), locations (indoor and outdoor), and durations (ie, from a single match to a week of tournament play). Such variations in daily demands can impact a player`s energetic requirements, thereby necessitating changes to total daily energy intake. Indeed, we recently reported the variability in total energy expenditure (TEE) by observing an approximately 50% increase for an elite singles male player (career high-ranking Association of Tennis Professionals [ATP] top 15) between a week involving 1 ATP match (3712 kcal·d-1) and a week comprising 5 matches (5520 kcal·d-1).1 Similarly, TEE was lower during a week of 3 Women`s Tennis Association (WTA) International matches (3383 kcal·d-1) when compared with a week of 5 Grand Slam tournament matches (3824 kcal·d-1) in an elite female player (career high-ranking WTA top 5). Such observations were the first direct assessment of energy expenditure of elite players using the doubly labeled water (DLW) method and position tennis as a highly energetically demanding sport (eg, 84 kcal·kg-1 and 71 kcal·kg-1 fat-free mass [FFM] for the male and female players, respectively).